A construção da identidade institucional do Arquivo Público da Cidade de Belo Horizonte: 1991-2021 - Daniele Augusta dos Santos Silva (2023)
This work aimed to study the development of the institutional identity of the Arquivo Público da Cidade de Belo Horizonte (APCBH), as a site of memory of the city. The time frame adopted comprised the first thirty years of the institution (1991 - 2021). The methodology used was a case study on the history of the entity combined with a bibliographic review and content analysis based on the outhread actions carried out. The bibliographic selection carried out included theoretical aspects of archival science and communication theory. Documentary research was also carried out in the subfund of the Directorate of the Belo Horizonte City Public Archive, from the primary and secondary activities of the Archive and also the closed fund of the APCBH Cultural Association. External materials to the institution were also researched, seeking to understand the institutional identity of the APCBH. Through the analysis carried out, it was noticed that the APCBH, in some actions, places itself as a guardian of the city's memory. This is due to its position of little prominence within the administrative structure of the Belo Horizonte City Hall, due to the difficulty in consolidating itself as an agency responsible for the management of administrative documents, due to the need to use cultural funding projects to develop some of its activities and needing to use the memorial justification.